Rabbi Abraham Ibn Ezra's commentary on Books 3-5 of Psalms, chapters 73-150 - Ibn Ezra, Abraham ben Meïr, 1089-1164 (New York, NY : Touro College Press ; Brighton, MA : Academic Studies Press, 2016)
Rabbi Abraham ibn Ezra's commentary is one of the great biblical exegeses produced by medieval Jewry. His commentary accompanies almost every version of the Rabbinic Bible, and his influence on biblical studies continues to this very day. Ibn Ezra sought to provide the literal meaning of the biblical text. However, he did more than that. His commentary is saturated with insights into Hebrew grammar, medieval philosophy, and astrology. Rabbi Abraham ibn Ezra's Commentary on Books 3-5 of Psalms: Chapters 73-150 completes the publication of the translation and annotation of Ibn Ezra's commentary to Psalms, making it available to both scholars and general readers.
Pages:1 to 29; Pages:30 to 58; Pages:59 to 87; Pages:88 to 116; Pages:117 to 145; Pages:146 to 174; Pages:175 to 203; Pages:204 to 232; Pages:233 to 261; Pages:262 to 290; Pages:291 to 319; Pages:320 to 348; Pages:349 to 377; Pages:378 to 406; Pages:407 to 435; Pages:436 to 464; Pages:465 to 493; Pages:494 to 522; Pages:523 to 551; Pages:552 to 580; Pages:581 to 596.
Online resource; title from digital title page (viewed on April 26, 2016).
eBooks on EBSCOhost
Keywords: Bible. -- Commentaries -- Early works to 1800.; Bible; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Biblical Studies -- Wisdom Literature; Commentaries; Early works